Relevansi Karya Sastra Pinocchio Dalam Pembentukan Karakter Siswa Sekolah Dasar - Fifin Norma Sari; Yeni Oktafiya (PT. Nawa Edukasi Nusantara, 2025)
This study is motivated by the importance of implementing character education from an early age to shape and instill values in students through literary works. The literary work discussed in this research is Pinocchio by Carlo Collodi. The author believes that the story of Pinocchio has a strong relevance in teaching character education that is engaging for students. This article also aims to explore the relevance of the Pinocchio story for elementary school students. This research is categorized as a library research study, where data collection is done by gathering information from various sources, both preliminary and secondary, such as books and articles that discuss character formation through children's stories. The results of the study indicate that the literary work Pinocchio is highly relevant in supporting character development for elementary school students. The story uses language that is easy for students to understand, an engaging plot, and contains many moral messages that can be learned by elementary school students.